Metal-coordinated fluorescent and luminescent probes for reactive oxygen species (ROS) and reactive nitrogen species (RNS) - Kwon, Nahyun; Kim, Dayeh; Swamy, K.M.K.; Yoon, Juyoung (Coordination chemistry reviews, 2021)
[Display omitted] •Recent advances in fluorescent and luminescent probes for ROS and RNS are discussed.•Metal-coordinated ROS- and RNS- selective probe systems are covered.•The categories of this review are H2O2, •OH, 1O2, O2•–, HOCl, ONOO−, NO/NO2, and HNO. Reactive oxygen species(ROS) are chemically reactive speciescontaining oxygen, which are produced from molecular oxygen (O2) during vital processes occurring in humans and other living organisms. These species include hydrogen peroxide (H2O2), hypochlorous acid/hypochlorite (HOCl/ClO–), hydroxyl radicals (OH), superoxide anion radicals (O2–) and singlet oxygen (1O2). ROS play key roles in various signaling and pathological processes and are essential to human life, but overproduction of ROS by exogenous stimuli is harmful because ROS can induce oxidation of DNA, proteins or lipids, resulting in cell death. Therefore, unusual ROS levels can indicate ailments such as Parkinson’s and Alzheimer’s diseases, inflammation, diabetes and cancer. Reactive nitrogen species (RNS) are another group of important chemically reactive species, which can damage cells via nitrosative stress. RNS include nitric oxide (NO), nitroxyl (HNO), nitrogen dioxide (NO2) and peroxynitrite (ONOO–). Due to their importance in human life, research into fluorescent and luminescent sensing and imaging of these ROS and RNS has been very active over the last couple of decades. Metal ions play key roles in the probes as an on–off redox switch for photoinduced quenching and as a reaction site with ROS, RNS or luminescent cores. Metal coordination reports the presence of analyte by changing the fluorescence intensity, lifetime, or excitation/emission maxima. Redox-active metal ions can be trigger switches that control fluorescence quenching effects, which can be used to sense ROS or RNS. In addition, metal ions, especially lanthanide metal ions, can often be themselves a source of light emission. In this review, we cover ROS- and RNS-selective fluorescent and luminescent probes based on metal-coordinated systems. This review is organized by the target ROS or RNS, which are H2O2, HOCl/ClO–, OH, O2–, 1O2, NO, ONOO–, HNO and NO2.